Psychostimulant Drugs and Neuroplasticity - Emilio Fernandez-Espejo; Nieves Rodriguez-Espinosa (MDPI AG, 2011)
Drugs of abuse induce plastic changes in the brain that seem to underlie addictive phenomena. These plastic changes can be structural (morphological) or synaptic (biochemical), and most of them take place in the mesolimbic and mesostriatal circuits. Several addiction-related changes in brain circuits (hypofrontality, sensitization, tolerance) as well as the outcome of treatment have been visualized in addicts to psychostimulants using neuroimaging techniques. Repeated exposure to psychostimulants induces morphological changes such as increase in the number of dendritic spines, changes in the morphology of dendritic spines, and altered cellular coupling through new gap junctions. Repeated exposure to psychostimulants also induces various synaptic adaptations, many of them related to sensitization and neuroplastic processes, that include up- or down-regulation of D1, D2 and D3 dopamine receptors, changes in subunits of G proteins, increased adenylyl cyclase activity, cyclic AMP and protein kinase A in the nucleus accumbens, increased tyrosine hydroxylase enzyme activity, increased calmodulin and activated CaMKII in the ventral tegmental area, and increased deltaFosB, c-Fos and AP-1 binding proteins. Most of these changes are transient, suggesting that more lasting plastic brain adaptations should take place. In this context, protein synthesis inhibitors block the development of sensitization to cocaine, indicating that rearrangement of neural networks must develop for the long-lasting plasticity required for addiction to occur. Self-administration studies indicate the importance of glutamate neurotransmission in neuroplastic changes underlying transition from use to abuse. Finally, plastic changes in the addicted brain are enhanced and aggravated by neuroinflammation and neurotrophic disbalance after repeated psychostimulants.